Loisir et intégration des immigrants : revue systématique des écrits sur le domaine et analyses autour des paradigmes de multiculturalisme et d'interculturalisme dans le contexte canadien. Issue 2 (4th May 2019) - Roult, Romain; White, Bob; Adjizian, Jean-Marc; Morel-Michaud, Laurianne; Auger, Denis
Abstract : The issue of immigrant integration is at the heart of many debates within contemporary industrialized societies. It has often been questioned and studied from the point of view of work, education, and health and social services. However, leisure is increasingly seen as a factor of integration for these immigrant populations. Thus, based on a systematic review of scientific literature ( n  = 63), this study allows us to sum up the current knowledge with regard to this issue. Beyond the fact that leisure is undeniably a factor in the social integration of immigrants, this study highlights the numerous obstacles and constraints that these populations experience when it comes to leisure, while, at the same time, emphasizing the benefits of the practice of recreational activities. This study has also shown the importance of considering the social dynamics between majority and minority groups with relation to the paradigms and approaches in which they move (multiculturalism and interculturalism, in particular).